APA Handbook of Psychology, Religion, and Spirituality (Vol 1): Context, Theory, and Research. 2013
DOI: 10.1037/14045-007
|View full text |Cite
|
Sign up to set email alerts
|

Religion, spirituality, and attachment.

Abstract: An individual who has been fortunate in having grown up in an ordinary good home with ordinarily affectionate parents has always known people from whom he can seek support, comfort, and protection, and where they are to be found. So deeply established are his expectations and so repeatedly have they been confirmed that, as an adult, he finds it difficult to imagine any other kind of world. (Bowlby, 1973, p. 208) RELIGION AND SPIRITuALITY CAPITALIZE ON THE OPERATION OF THE ATTACHMENT SYSTEMAttachment refers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 42 publications
9
109
0
1
Order By: Relevance
“…The theory posits a kind of infant socialization process that translates the infant/caregiver relationship into patterns of relational expectation housed in what are called internal working models (IWMs). Individuals experience their IWMs as a complex of social, emotional, neurological, and biological events used to form expectations of what may or may not be received in future attachment relationships (Granqvist and Kirkpatrick ).…”
Section: Introductionmentioning
confidence: 99%
“…The theory posits a kind of infant socialization process that translates the infant/caregiver relationship into patterns of relational expectation housed in what are called internal working models (IWMs). Individuals experience their IWMs as a complex of social, emotional, neurological, and biological events used to form expectations of what may or may not be received in future attachment relationships (Granqvist and Kirkpatrick ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this theory, emerging research has found a correspondence between the quality of an individual's parental attachments and attachments to God (Granqvist and Kirkpatrick, 2013). Thus secure attachments to parents are often tied to a secure felt connection to the Divine.…”
Section: Promising Theoretical Advancesmentioning
confidence: 83%
“…Yet psychological research clarifies the process of spiritual seeking, particularly when situations of threat, loss, or challenge motivate the spiritual search. In these situations, as causes and outcomes are questioned, meaning becomes salient (Spilka et al 1985); self-transformation is typically sought (e.g., through psychotherapy or religious conversion); corresponding changes in meaning-systems occur (Paloutzian 2005); and relationships with others, including spiritual relationships, are intensified (Granqvist and Kirkpatrick 2013). …”
Section: Psychology Informs Understandings Of Spiritualitymentioning
confidence: 99%